Exploring Dual-Task Performance Relationships for Veterans with Lower-Limb Amputation. - Swink, L. A.; So, N.; Nearing, K. A.; Juarez-Colunga, E.; Plummer, P.; Schmid, A. A.; Christiansen, C. L. (Occupational Therapy in Health Care, 2025)
Adults with lower-limb (LL) amputation have difficulty dual-tasking which may elicit falls and is required for instrumental activities of daily living (IADLs). The purpose of this study was to explore the relationships between dual-task performance, falls, and IADLs for Veterans with LL amputation. A cross-sectional study was completed with dual-task performance, retrospective fall reporting, and participation in IADLs. Dual-task performance varied across participants (n = 24) and although it was not significantly correlated to IADL participation, the relationships between dual-tasking, falls, and IADLs warrants further study to maximize dual-task training that can translate to everyday life.